Congenital laryngoptosis: An unusual case - Eyibilen, Ahmet; Aladag, Ibrahim; Kocakoc, Ercan (Elsevier Taiwan, 2011)
Laryngoptosis is a rare anomaly of the larynx. The larynx is localized in a position lower than its normal position. A 15-year-old boy presented with hoarseness of voice. Physical examination showed that the larynx was in an abnormal position. There were no palpated tracheal rings. A low-pitched monotonic voice was the only symptom of laryngoptosis. Magnetic resonance imaging showed that the larynx was almost localized on the manibrium sterni, and the diagnosis was laryngoptosis. Copyright (C) 2011, Elsevier Taiwan LLC. All rights reserved.
Keywords: Congenital anomalies of the larynx; Congenital laryngoptosis; Hoarseness